Surveillance of device associated infections in intensive care units at a Saudi Arabian Hospital, 2017-2020 - Jaffar A. Al-Tawfiq; Rana Abdrabalnabi; Alla Taher; Shantymole Mathew; Sami Al-Hassan; Halima AlRashed; Saeed S. Al-Yami (Elsevier, 2023)
Background: Device-associated infections (DAIs) are important components of healthcare associated infection and are associated with increased morbidity and mortality. This study describes DAIs across different intensive care units (ICUs) in a hospital in Saudi Arabia. Methods: The study was conducted between 2017 and 2020 and followed the definitions of National Healthcare Safety Network (NHSN) for DAIs. The calculated the rates of ventilator-associated events (VAE), catheter-associated urinary tract infections (CAUTI) and central line-associated blood stream infections (CLABSI) followed NHSN definitions. Results: During the study period, there were 82 DAIs in adult ICUs and of these 16 (19.5%) were CLABSI, 26 (31.7%) were CAUTI and 40 (48.7%) were VAE. The overall rates for adult ICUs were 1.6, 1.9, 3.8 per 1000 device-days for CAUTI, CLABSI and VAE, respectively. The device-utilization ratio was 0.5, 0.6, and 0.48 for urinary catheters, central lines, and ventilators, respectively. VAE rates for medical and surgical ICU were about 2.8 times the rate in the coronary care unit and the rates were high in 2020 corresponding with the COVID-19 pandemic. Of the adult ICUS, medical ICU had a CLABSI rate of 2.13/1000 device-days and was about double the rate in surgical and cardiac ICU. For CAUTI, the rates per 1000 device-days were 2.19, 1.73, and 1.65 for medical, surgical, and coronary ICUs, respectively. The rate of CLABSI per 1000 device-days for pediatric and neonatal ICUs were 3.38 and 2.28, respectively. Conclusions: CAUTI was the most common infections among adult ICUs and medical ICU had higher rates than other adult ICUs. VAE rate was higher in the first year of the COVID-19 pandemic, indicating increased device-use, change in patients characteristics as well as possible change in practices across the ICUs.